Gabriel’s Epiphany and the End of Resentment: Religious Feeling in James Joyce’s The Dead - Fashbaugh, Martin (Anthropoetics, 2022)
This article supports three interconnected points regarding James Joyce’s “The Dead.” First, the paper shows mimetic desire’s importance in the early formation of an aesthetic experience. Gabriel Conway’s realization that his wife Gretta has been harboring a romantic passion for the long-dead Michael Furey naturally stimulates jealousy, which is a consequence of his mimetic desire. Second, this essay examines how Gabriel chooses, perhaps instinctually, to respond to this mimetic circumstance constructively rather than destructively through the abortive gesture of appropriation. Third, I argue that Gabriel’s deferral of violence in favor of symbolic appropriation is a spiritual and religious event that moves far beyond the personal. He symbolically appropriates not only Gretta and Furey but essentially the whole of Ireland, creating this feeling of oneness and inseparability which often grounds religious experience. However, I also point out that this transcendence is likely a tentative one, for the glorious vision of appropriating the entirety of the Irish “dead” suggests Gabriel is quite ambitious and prone to jealousy and feelings of inadequacy. While making these three primary points, I also discuss the role the epiphany plays in the recreation of the originary scene. I argue that Gabriel’s epiphany, which is that both his marriage and life have been, for the most part, dispassionate, helps to facilitate the transition from mimetic desire to the symbolic acquisition of the originary scene.